If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -8 + x + 54 = 5 + 5x + 45 + -2x Reorder the terms: -8 + 54 + 4x + x = 5 + 5x + 45 + -2x Combine like terms: -8 + 54 = 46 46 + 4x + x = 5 + 5x + 45 + -2x Combine like terms: 4x + x = 5x 46 + 5x = 5 + 5x + 45 + -2x Reorder the terms: 46 + 5x = 5 + 45 + 5x + -2x Combine like terms: 5 + 45 = 50 46 + 5x = 50 + 5x + -2x Combine like terms: 5x + -2x = 3x 46 + 5x = 50 + 3x Solving 46 + 5x = 50 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 46 + 5x + -3x = 50 + 3x + -3x Combine like terms: 5x + -3x = 2x 46 + 2x = 50 + 3x + -3x Combine like terms: 3x + -3x = 0 46 + 2x = 50 + 0 46 + 2x = 50 Add '-46' to each side of the equation. 46 + -46 + 2x = 50 + -46 Combine like terms: 46 + -46 = 0 0 + 2x = 50 + -46 2x = 50 + -46 Combine like terms: 50 + -46 = 4 2x = 4 Divide each side by '2'. x = 2 Simplifying x = 2
| 6(x+5)-(3x-4)= | | 3(2x-5)+2=(3x-1)-2(x-4) | | 5.22-1.34x=4x-0.921 | | 8x+4=12x-9 | | 3(4z-7)+8(2z+4)=0 | | 5p+yr=r-6g | | 5y-5=y-12+7y | | (16b-6)-5(3b+3)=-3 | | 5(x-4)+3x-9x=6-(2x-5)+8x | | 0.6x+0.8660y-784.8=0 | | x*x-2=11 | | -5+3v=3v-5 | | 2x+7y=18 | | X-5=-54 | | 9s+12s+4=0 | | -13+5x=4x-7-2 | | 4x-17=4x+16 | | d=4.7+2.8(7.4) | | x*x-2=31 | | 6n+8=6n | | 8y+8=7y-2 | | -8x-x=-16-x | | d=4.7+2.8(12) | | 15+5m=-1+3m | | -3-6v=-v-6v | | =.8(x-25) | | 2.10+12.99b=12.39 | | -9+2k=-2k+7k | | -8a+6a=-2-4a | | 8n-4=-4+8n | | 4cosx+3sinx=y | | 5(X-15)2=75 |